Processing Effect on Anti-nutritional Factors and Phytochemicals of Horse gram (Macrotyloma uniflorun) Flour. - Ojha, P. (Tufts University. Tisch Library., 2019)
This poster shows Processing effect on Anti-nutritional factors and Phytochemicals of horse gram flour.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy